Quality of Evidence Supporting the Role of Tripterygium Glycosides for the Treatment of Diabetic Kidney Disease: An Overview of Systematic Reviews and Meta-Analyses - Shi H; Deng P; Dong C; Lu R; Si G; Yang T (Dove Medical Press, 2022)
Hongshuo Shi,1,* Pin Deng,2,* Chengda Dong,3 Rongchen Lu,1 Guomin Si,4 Tiantian Yang4 1College of Traditional Chinese Medicine, Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of China; 2The Third Affiliated Hospital of Beijing University of Chinese Medicine, Beijing, People's Republic of China; 3First Clinical Medical College, Shandong University of Traditional Chinese Medicine, Jinan, People's Republic of China; 4Department of Traditional Chinese Medicine, Provincial Hospital Affiliated to Shandong First Medical University, Jinan, People's Republic of China*These authors contributed equally to this workCorrespondence: Tiantian Yang, Email ytt@bucm.edu.cnBackground: Tripterygium glycosides (TG) is widely used in the treatment of diabetic kidney disease (DKD) in China. To systematically assess and synthesize the available evidence, we present an overview of systematic reviews (SRs) and meta-analyses (MAs) on the topic of TG interventions for DKD.Methods: SRs/MAs on TG interventions for DKD were comprehensively searched in seven databases. Methodological quality, risk of bias, reporting quality, and quality of evidence were assessed using the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2), the Risk of Bias in Systematic (ROBIS) scale, the list of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), as well as the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system.Results: This overview includes 13 SRs/MAs that use quantitative calculations to comprehensively assess various outcomes in TG interventions for DKD. The methodological quality, reporting quality, and risk of bias of SRs/MAs, and the quality of evidence for outcome indicators are unsatisfactory. Limitations of the included SRs/MAs consist in the lack of essential procedures such as protocol registration, screening of duplicate study, provision of the list of excluded studies, and assessment of publication bias. Besides, the reliance on small samples for quantitative synthesis of effect sizes also constitutes an important limitation.Conclusion: TG may be a potential complementary treatment modality to DKD therapy. However, this conclusion must be treated with caution as the quality of the evidence provided by SRs/MAs is generally low.Keywords: tripterygium glycosides, diabetic kidney disease, systematic reviews, meta-analyses, overview